A rare homozygous p.Arg87Trp variant of the GBA gene in Gaucher disease: A case report - Houweyda Jilani; Faten Hsoumi; Imen Rejeb; Yasmina Elaribi; Syrine Hizem; Molka Sebai; Arndt Rolfs; Lamia Benjemaa (Clinical Case Reports, 2022)
Abstract Gaucher disease (GD) is a rare metabolic disorder due to pathogenic variants in the GBA gene. We report the first case of the rare p.Arg87Trp pathogenic variant (formerly known as R48W) of the GBA gene in the Tunisian population. A female Arab patient was assessed at the age of 26 due to abdominal distension, bone pain, and headache since she was 25. Physical examination revealed splenomegaly, rib deformation, lumbar scoliosis, and upper limb tremor. Bone marrow was infiltrated by Gaucher cells. The patient was homozygous for the rare p.Arg87Trp variant which is known to be associated with a mild phenotype. This report highlights the necessity of screening the Tunisian population for this rare variant.